Method for preparing ozone catalyst by compounding lithium smelting slag and aluminum tailing slag, ozone catalyst and application

CN122912902APending Publication Date: 2026-10-16PINGXIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610863610.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-15
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

但通常采用单一的锂冶炼渣进行催化及载体的制备时由于Al含量较低,一般采用额外添加Al源的方法,例如,有采用稀土尾矿进行A沸石制备时采用额外添加Al源的方法,这种方法会导致更高的经济成本

Benefits of technology

[0017]This disclosure presents a method for preparing an ozone catalyst using a composite of lithium smelting slag and aluminum tailings, the ozone catalyst itself, and its applications. The method includes: sequentially ball-milling and sieving the lithium smelting slag and aluminum tailings; adding an alkali activator, bentonite, and fiber powder to the treated lithium smelting slag and aluminum tailings to obtain a composite slag masterbatch; adding water to the composite slag masterbatch and stirring until homogeneous, followed by granulation and drying to obtain a catalyst; sintering the catalyst and cooling it to room temperature to obtain a catalyst support; immersing the catalyst support in a ferrous nitrate solution and stirring, then drying and activating it to obtain an impregnated metal support; and calcining the impregnated metal support to obtain the ozone catalyst. This disclosure is the first to use a coordinated method of combining lithium smelting slag and aluminum tailings to prepare an ozone catalyst, which not only achieves high-value resource utilization of solid waste but also solves the problem of adding an additional Al source, reducing costs. Simultaneously, by adjusting the proportions, different types of ozone catalysts can be prepared for the treatment of recalcitrant organic pollutants and heavy metal Pb in landfill leachate. 2+ Application verification was conducted on the adsorption of [the substance].

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912902A_ABST
    Figure CN122912902A_ABST
Patent Text Reader

Abstract

The present disclosure provides a method for preparing an ozone catalyst by compounding lithium smelting slag and aluminum tailings, an ozone catalyst and an application, belonging to the technical field of resource utilization of multiple tailings. The method comprises sequentially ball milling and sieving the lithium smelting slag and the aluminum tailings; adding an alkali activator, bentonite and fiber powder to the treated lithium smelting slag and aluminum tailings to obtain a composite slag masterbatch; uniformly stirring the composite slag masterbatch with water, granulating and drying to obtain a catalyst; sintering the catalyst, and cooling to room temperature to obtain a catalyst carrier; immersing the catalyst carrier in a ferrous nitrate solution and stirring, then taking out and drying and activating to obtain an impregnated metal carrier; and roasting the impregnated metal carrier to obtain an ozone catalyst. The method not only realizes high-value resource utilization of solid waste, but also solves the problem of additional Al source and reduces cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure belongs to the field of resource utilization technology of various tailings, specifically involving a method for preparing an ozone catalyst by compounding lithium smelting slag and aluminum tailings, the ozone catalyst and its application. Background Technology

[0002] Layered aluminosilicate lepidolite is the most common lithium mineral and one of my country's richest lithium resources. However, due to its low grade (Li₂O in the raw ore: 0.3%~0.6%), the waste rate is as high as 99.5%, including approximately 90% tailings (lithium slag) and 9.5% lithium smelting slag. Unlike lithium slag (beneficiation slag), lithium smelting slag is the waste generated after solid-liquid separation of lithium concentrate (lepidolite concentrate or spodumene concentrate) through roasting and leaching to extract lithium, and its composition is more complex. In the process of extracting Li using the sulfate roasting method, K₂SO₄, Na₂SO₄, and CaSO₄ are added during the pyrometallurgical roasting process, and the sintering temperature is controlled at approximately 1000℃ (the melting point of lepidolite is 903℃), so that CaSO₄ at high temperature... 2+ Na + and K + After solid-phase ion exchange with Li+ in lepidolite to obtain water-soluble LiSO4 and thus extracting Li, the remaining impurities and salt components will exist in the lithium smelting (leaching) slag. This process has a waste rate as high as 2.5 × 10⁻⁶. 5 The concentration of lithium mica is approximately 1000 t / t·LiCO3. Therefore, other metallic components in lepidolite accumulate as sulfates in lithium smelting slag, causing significant environmental impact during natural stockpiling. Furthermore, the presence of metal sulfates and high sulfur content lead to salt precipitation and cracking issues in its use in cement, concrete, and other construction industries, hindering resource utilization.

[0003] The resource utilization of lithium smelting slag has become a research hotspot. It can be used to prepare microcrystalline glass, cement materials, geopolymers, industrial ceramic materials, etc., without being affected by sulfur content and metal sulfates.

[0004] High-performance ozone catalysts in industrial ceramics play a crucial role in the advanced oxidation of recalcitrant organic pollutants. Besides typical recalcitrant organic wastewater from chemical, dyeing, and landfill leachate industries, national policies requiring the upgrading and transformation of wastewater treatment facilities are driving wastewater treatment plants across the country towards a "new concept plant" focused on circular economy and sustainable development, encompassing reclaimed water utilization, energy recycling, and resource recovery. Current policies require wastewater treatment plants nationwide to add advanced oxidation processes at the end of their biological treatment processes to remove recalcitrant organic pollutants and trace heavy metals from the effluent. Therefore, the market for ozone catalysts is vast.

[0005] XRD analysis revealed that the main phases of lithium smelting slag include quartz (SiO2), gypsum (CaSO4·2H2O), calcite (CaCO3), and amorphous SiO2 and Al2O3, making it suitable for ozone catalyst support preparation. However, when using lithium smelting slag alone for catalysis and support preparation, the low Al content necessitates the addition of an additional Al source. For example, this method is sometimes used when preparing A-zeolite from rare earth tailings, leading to higher economic costs. Furthermore, the complex composition of lithium smelting slag makes preparation difficult, especially with the interference of metal sulfates, which hinders molding and results in insufficient compressive strength for the catalyst support. Summary of the Invention

[0006] This disclosure aims to at least solve one of the technical problems existing in the prior art, and to provide a method for preparing an ozone catalyst by compounding lithium smelting slag and aluminum tailings, the ozone catalyst and its application.

[0007] One aspect of this disclosure provides a method for preparing an ozone catalyst using a compound of lithium smelting slag and aluminum tailings, the method comprising: Lithium smelting slag and aluminum tailings were sequentially ball-milled and sieved. Alkali activator, bentonite, and fiber powder are added to the treated lithium smelting slag and aluminum tailings to obtain composite slag masterbatch. Water is added to the composite slag masterbatch and stirred evenly. After granulation and drying, a catalyst is obtained. The catalyst is sintered and then cooled to room temperature to obtain a catalyst support. The catalyst support was immersed in a ferrous nitrate solution and stirred. After being removed, it was dried and activated to obtain an impregnated metal support. The impregnated metal support is calcined to obtain an ozone catalyst.

[0008] Optionally, the contents of the lithium smelting slag and the aluminum tailings are calculated as SiO2 and Al2O3, respectively, and the molar ratio of the two is n(SiO2 / Al2O3)=(1.1-1.2):1; The contents of the lithium smelting slag and the alkali activator are calculated as SiO2 and Na2O, respectively, and the molar ratio of the two is n(SiO2 / Na2O) = (2.5~3):1; The total content of lithium smelting slag and aluminum tailings to the amount of bentonite added is in a mass ratio of 6.5:(1~3); The mass ratio of the total content of lithium smelting slag and aluminum tailings to the amount of fiber powder added is 6.5:(1~3).

[0009] Optionally, the particle size of the catalyst after granulation is 3-6 mm, and the drying temperature is 100-110℃ for 10-14 h.

[0010] Optionally, the sintering treatment of the catalyst includes: Increase the temperature to 350-450℃ at 5℃ / min, hold for 1.5-2.5 h, then continue to increase the temperature to 750-850℃ at 5℃ / min, hold for 1.5-2.5 h.

[0011] Optionally, the catalyst support is immersed in a ferrous nitrate solution and stirred at a speed of 200-300 r / min for 2-3 h.

[0012] Optionally, the drying temperature after removal is 100-110℃, and the activation temperature is 90-100℃ for 1-2 hours.

[0013] Optionally, the impregnated metal carrier is subjected to a calcination treatment, including: Calcination is carried out at a rate of 5℃ / min to 350-450℃, and the temperature is maintained for 1.5-2.5 hours.

[0014] In another aspect of this disclosure, an ozone catalyst is provided, which is prepared using the method described above.

[0015] Optionally, the ozone catalyst has a dodecahedral and octahedral single crystal structure with a particle size of 3-5 mm and a bulk density of 0.65-0.75 g / ml.

[0016] In another aspect of this disclosure, an application of an ozone catalyst is proposed for use in landfill leachate containing recalcitrant organic pollutants and Pb. 2+ In the adsorption.

[0017] This disclosure presents a method for preparing an ozone catalyst using a composite of lithium smelting slag and aluminum tailings, the ozone catalyst itself, and its applications. The method includes: sequentially ball-milling and sieving the lithium smelting slag and aluminum tailings; adding an alkali activator, bentonite, and fiber powder to the treated lithium smelting slag and aluminum tailings to obtain a composite slag masterbatch; adding water to the composite slag masterbatch and stirring until homogeneous, followed by granulation and drying to obtain a catalyst; sintering the catalyst and cooling it to room temperature to obtain a catalyst support; immersing the catalyst support in a ferrous nitrate solution and stirring, then drying and activating it to obtain an impregnated metal support; and calcining the impregnated metal support to obtain the ozone catalyst. This disclosure is the first to use a coordinated method of combining lithium smelting slag and aluminum tailings to prepare an ozone catalyst, which not only achieves high-value resource utilization of solid waste but also solves the problem of adding an additional Al source, reducing costs. Simultaneously, by adjusting the proportions, different types of ozone catalysts can be prepared for the treatment of recalcitrant organic pollutants and heavy metal Pb in landfill leachate. 2+ Application verification was conducted on the adsorption of [the substance]. Attached Figure Description

[0018] Figure 1 This is a flowchart illustrating a specific embodiment of the method for preparing an ozone catalyst using a compound of lithium smelting slag and aluminum tailings. Figure 2 This is a physical image of the ozone catalyst prepared by combining lithium smelting slag and aluminum tailings according to Example 1 of this disclosure. Figure 3 This is a graph showing the relationship between the compressive strength of the ozone catalyst before and after activation and the amount of bentonite added in Examples 1-5 of this disclosure; wherein, Figure 3 (a) in the diagram represents the result before activation. Figure 3 (b) in the figure represents the result after activation; Figure 4 The images show three-dimensional fluorescence spectra of the ozone catalysts used in Examples 1-5 of this disclosure to remove recalcitrant organic pollutants; wherein, Figure 4 (a) in the text represents the effluent after biochemical treatment of landfill leachate. Figure 4 (b) in the image represents the wastewater after being adsorbed by an ozone catalyst prepared from lithium smelting slag + aluminum tailings: bentonite = 6.5:1. Figure 4 (c) in the text refers to the wastewater after being adsorbed by an ozone catalyst prepared from lithium smelting slag + aluminum tailings: bentonite = 6.5:1.5. Figure 4 In the text, (d) represents the wastewater after being adsorbed by an ozone catalyst prepared from lithium smelting slag + aluminum tailings: bentonite = 6.5:2. Figure 4 In the diagram, (e) represents the wastewater after adsorption by an ozone catalyst prepared from lithium smelting slag + aluminum tailings: bentonite = 6.5:2.5. Figure 4In the text (f), the wastewater is the landfill leachate tailwater after being adsorbed by an ozone catalyst prepared from lithium smelting slag + aluminum tailings: bentonite = 6.5:3. Figure 5 The zeolite product obtained in Example 1 of this disclosure is effective against Pb. 2+ The maximum adsorption capacity and removal efficiency are shown in the graph. Figure 6 The image shows the SEM image of the ozone catalyst obtained in Example 1 of this disclosure. Figure 7 The XRD pattern of the ozone catalyst obtained in Example 1 of this disclosure; Figure 8 This is a photograph of the ozone catalyst prepared separately from lithium smelting slag, which is Comparative Example 1 of this disclosure. Detailed Implementation

[0019] To enable those skilled in the art to better understand the technical solutions of this disclosure, the disclosure will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain this disclosure and represent a part of the embodiments of this disclosure, not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this disclosure without creative effort are within the protection scope of this disclosure.

[0020] As shown in Figure 1, one aspect of this disclosure provides a method S100 for preparing an ozone catalyst using lithium smelting slag and aluminum tailings, specifically including the following steps S110~S160: S110, Pretreatment: Lithium smelting slag and aluminum tailings are sequentially ball-milled and passed through a 200-mesh sieve.

[0021] It should be noted that the Al2O3 content in aluminum tailings is 63.06%, which can be compounded with lithium smelting slag to adjust the silicon / aluminum ratio and prepare a highly stable ozone catalyst support without the need for additional aluminum source.

[0022] S120, Raw material compounding: Alkali activator, bentonite, and fiber powder are added to the treated lithium smelting slag and aluminum tailings to obtain composite slag masterbatch.

[0023] In step S120, the contents of lithium smelting slag and aluminum tailings are calculated as SiO2 and Al2O3, respectively, and the molar ratio of the two is n(SiO2 / Al2O3) = (1.1-1.2):1.

[0024] In step S120, the contents of lithium smelting slag and the alkaline activator are calculated as SiO2 and Na2O, respectively, and their molar ratio n(SiO2 / Na2O) = (2.5~3):1. The alkaline activator can be Na2O, NaOH, NaCO3, etc.

[0025] In step S120, the mass ratio of the total content of lithium smelting slag and aluminum tailings to the amount of bentonite added is 6.5:(1~3).

[0026] In step S120, the mass ratio of the total content of lithium smelting slag and aluminum tailings to the amount of fiber powder added is 6.5:(1~3).

[0027] This step uses high-alumina aluminum tails to compensate for insufficient aluminum content in lithium smelting slag, precisely controls the silicon-aluminum ratio, and generates catalyst carrier precursors in situ. It eliminates the need for external industrial alumina, solves the problems of aluminum deficiency and cracking in single lithium slag, and significantly reduces raw material procurement costs.

[0028] Furthermore, the alkaline environment provided disrupts the silicon-aluminum bonds, activating amorphous silicon-aluminum and promoting the formation of a porous FAU molecular sieve framework during calcination, which helps increase the specific surface area and the number of active sites. Simultaneously, the minerals can be activated at low temperatures, eliminating the need for high-temperature, strong acid pretreatment and reducing energy consumption.

[0029] S130, Pelletizing and Drying: Water is added to the composite slag masterbatch and stirred evenly. After granulation and drying, catalyst carrier pellets are obtained.

[0030] In step S130, the water content is about 30 wt.% of the composite slag masterbatch, and then the catalyst is granulated with the particle size controlled at 3~6 mm. The prepared catalyst is placed in an electric heating blast drying oven and dried at 100-110℃ for 10-14 h.

[0031] S140. High-temperature sintering: The catalyst support pellets are sintered and then cooled to room temperature to obtain the catalyst support.

[0032] In step S140, the dried catalyst support pellets are placed in a muffle furnace for sintering. The temperature is increased to 350-450℃ at 5℃ / min and held for 1.5-2.5h. The temperature is then increased to 750-850℃ at 5℃ / min and held for 1.5-2.5h. After cooling to room temperature, the catalyst support is obtained.

[0033] This step first involves evaporating the fibers and organic matter at 350-450℃ to create pores, and then crystallizing the silicon and aluminum at 750-850℃ to form a molecular sieve support framework, resulting in a stable framework structure.

[0034] S150, Impregnation and Activation: The catalyst support is immersed in ferrous nitrate solution and stirred. After being taken out, it is dried and activated to obtain an impregnated metal support.

[0035] In step S150, the carrier is immersed in a 1 mol / L ferrous nitrate solution using an impregnation method, stirred with a magnetic stirrer at 200-300 r / min for 2-3 h, removed and dried at 100-110℃, and then placed in a filter bag and activated in a water bath at (95±5)℃ for 1-2 h.

[0036] This step uses a liquid-phase uniformly loaded Fe 2+ The active component is activated by water bath, which promotes the entry of iron ions into the molecular sieve channels, ensuring uniform dispersion of the active component and preventing solid-phase co-firing and deactivation.

[0037] S160, Calcination and Cooling: The impregnated metal support is calcined to obtain an ozone catalyst.

[0038] In step S160, the dried impregnated metal carrier is placed in a muffle furnace and calcined at 350-450°C at a rate of 5°C / min for 1.5-2.5 hours.

[0039] This step converts ferrous iron into highly active iron oxide, forming ozone catalytic active sites. By heat-treating the support and active components in steps, the crystal forms of the support and the active crystal forms are not destroyed, which is beneficial to improving catalytic stability.

[0040] This disclosure is the first to employ a coordinated method combining lithium smelting slag and aluminum tailings to prepare ozone catalysts. This not only achieves high-value resource utilization of solid waste but also solves the problem of adding an additional Al source, reducing costs. Simultaneously, by adjusting the proportions, different types of ozone catalysts can be prepared for the treatment of recalcitrant organic pollutants and heavy metal Pb in landfill leachate biochemical effluent. 2+ Application verification was conducted on the adsorption of [the substance].

[0041] In another aspect of this disclosure, an ozone catalyst is proposed, which is prepared by the method described above. For details of the process, please refer to the above description, which will not be repeated here.

[0042] The ozone catalyst prepared in this disclosure has a dodecahedral and octahedral single crystal structure with a particle size of 3-5 mm and a bulk density of 0.65-0.75 g / ml.

[0043] In another aspect of this disclosure, an ozone catalyst is proposed for the removal of recalcitrant organic pollutants or Pb. 2+ In the adsorption.

[0044] The catalyst disclosed herein exhibits an internally formed FAU molecular sieve porous structure with a high specific surface area. In use, ozone is decomposed under the support of an iron-loaded active component to generate… OH radicals are strong free radicals that efficiently oxidize humic acid and other recalcitrant organic matter in landfill leachate. Secondly, the molecular sieve framework possesses abundant pores and surface hydroxyl groups and negatively charged active sites, enabling it to capture Pb in the effluent through a combination of physical adsorption and ion exchange. 2+ .

[0045] The method for preparing ozone catalysts by combining lithium smelting slag and aluminum slag will be further illustrated below with specific examples: Example 1 (1) Pretreatment: The lithium smelting slag and aluminum tailings were ball-milled and passed through a 200-mesh sieve in sequence before being put into use. (2) Raw material compounding: Lithium smelting slag and aluminum tailings were prepared according to a ratio of n(SiO2 / Al2O3) = 1.14:1. Add the alkaline activator NaOH according to n(SiO2 / Na2O)=2.56:1.

[0046] Add bentonite according to the mass ratio (lithium smelting slag + aluminum tailings : bentonite = 6.5 : 2).

[0047] Add fiber powder according to the mass ratio (lithium smelting slag + aluminum tailings : fiber powder = 13 : 1); The composite slag masterbatch was obtained and set aside for later use.

[0048] (3) Ball formation and drying After mixing the raw materials, add an appropriate amount of water (about 30 wt.%) and stir until homogeneous. Then granulate the mixture, controlling the particle size to 3-6 mm. Place the prepared catalyst in an electrically heated drying oven and dry it at 105℃ for 12 h.

[0049] (4) High-temperature sintering: The dried catalyst is placed in a muffle furnace for sintering. The temperature is increased to 400℃ at 5℃ / min and held for 2 h. The temperature is then increased to 800℃ at 5℃ / min and held for 2 h. After cooling to room temperature, the catalyst support is obtained.

[0050] (5) Impregnation activation The carrier was immersed in a 1 mol / L ferrous nitrate solution using an impregnation method, and stirred at 200 r / min for 2 h with a magnetic stirrer. It was then removed and dried at 105℃. The dried carrier was placed in a filter bag and activated in a water bath at 95℃ for 1 h.

[0051] (6) Calcination and cooling The dried impregnated metal carrier is placed in a muffle furnace and calcined at 400°C with a heating rate of 5°C / min, and held at that temperature for 2 hours.

[0052] like Figure 2As shown, the ozone catalyst prepared by compounding lithium smelting slag and aluminum slag in this embodiment has a smooth surface, is not easy to crack, has a particle size of 3~5mm, and a bulk density of 0.65~0.75g / ml.

[0053] like Figure 3 As shown, when the mass ratio of the narrow catalyst and the ozone catalyst is (lithium smelting slag + aluminum tailings: bentonite = 6.5:2), the maximum compressive strength before activation is 456.6 N / piece (average 364.6 N / piece), and the strength increases sharply. The compressive strength after activation is about 262.9 N / piece, which is greater than the national requirement of 150 N / piece.

[0054] like Figure 4 As shown in (a, d), with A 2 Taking the leachate effluent from the / O process as the research object, the concentration of degradable organic pollutants after biochemical treatment is low, but it is mainly composed of recalcitrant organic matter, which is typical and representative. Three-dimensional fluorescence spectroscopy revealed that the fluorescence peaks of the raw leachate are mainly concentrated in the humic acid-like region, indicating a high degree of humification and a large proportion of recalcitrant components. The ozone catalyst prepared with a mass ratio (lithium smelting slag + aluminum tailings : bentonite = 6.5 : 2) showed a significant effect on the removal of humic acid in the leachate, reducing the fluorescence intensity from >400 a.u. to 200 a.u., and significantly reducing the area of ​​the integral region.

[0055] like Figure 5 As shown in (a), the effect of solution pH on Pb 2+ The adsorption effect (pH=2, 3, 4, 5, 6, 7) results show that the adsorption performance increases with increasing pH in the pH range of 2-5, and decreases in the opposite direction above pH 5. Therefore, a treatment environment with pH=5 can be optimized. Furthermore, combined with... Figure 5 As shown in (b), the ozone catalyst prepared with a mass ratio of (lithium smelting slag + aluminum tailings : bentonite = 6.5 : 2) exhibits the following characteristics at pH 5, water temperature 25℃, dosage 10 g / L, and equilibration time 12 h: the adsorption capacity first increases and then decreases with increasing lead concentration (reaching its maximum at 800 mg / L); the removal rate continuously decreases with increasing concentration; it is suitable for the deep treatment of low-concentration lead-containing wastewater with a concentration ≤200 mg / L. 2+ The adsorption efficiency remained stable at over 90% when the initial wastewater concentration was 200 mg / L, and the calculated maximum adsorption capacity was 161.8 mg·g⁻¹. -1 This meets the adsorption capacity requirements of heavy metal adsorbents.

[0056] like Figure 6 and Figure 7 As shown, the ozone catalyst obtained under the preparation conditions of (lithium smelting slag + aluminum tailings: bentonite = 6.5:2) was characterized, and its specific surface area was 19.2383 m².2 / g, SEM and XRD showed that it mainly exists as dodecahedral and octahedral single crystals, corresponding to the FAU molecular sieve framework structure of SOD structure.

[0057] Example 2 The preparation process in this example is the same as in Example 1, except that bentonite is added according to the mass ratio (lithium smelting slag + aluminum tailings: bentonite = 6.5: 1).

[0058] like Figure 3 As shown, the compressive strength of the narrow catalyst and the ozone catalyst before activation was 15.6~88.3 N / piece (average 44.4 N / piece) when the mass ratio was (lithium smelting slag + aluminum tailings: bentonite = 6.5:1), which was the lowest strength, poor molding and easy to break. The average compressive strength after activation was 38.2 N / piece. If too little bentonite was added, the bonding skeleton was insufficient, and the compressive strength after activation was basically the same as that before activation.

[0059] like Figure 4 As shown in (b), the ozone catalyst prepared with a mass ratio of (lithium smelting slag + aluminum tailings: bentonite = 6.5: 1) has a significant effect on the removal of humic acid in landfill leachate, with the fluorescence intensity decreasing from >400 a.u to 250 a.u and the area of ​​the integral region decreasing.

[0060] Example 3 The preparation process in this example is the same as in Example 1, except that bentonite is added according to the mass ratio (lithium smelting slag + aluminum tailings: bentonite = 6.5: 1.5).

[0061] like Figure 3 As shown, when the mass ratio of the narrow catalyst and the ozone catalyst is (lithium smelting slag + aluminum tailings: bentonite = 6.5:1.5), the maximum compressive strength before activation is 200.1 N / particle (average 143.8 N / particle), which is a significant increase in strength. Due to the binding effect of bentonite, the average compressive strength after activation is 157.5 N / particle, which is still greater than the national requirement of 150 N / particle.

[0062] like Figure 4 As shown in (c), the ozone catalyst prepared with a mass ratio of (lithium smelting slag + aluminum tailings: bentonite = 6.5: 1.5) has a significant effect on the removal of humic acid in landfill leachate. The fluorescence intensity decreased from >400 a.u. to 285 a.u. and the area of ​​the integral region was greatly reduced.

[0063] Example 4 The preparation process in this example is the same as in Example 1, except that bentonite is added according to the mass ratio (lithium smelting slag + aluminum tailings: bentonite = 6.5: 2.5).

[0064] like Figure 3 As shown, when the mass ratio of the narrow catalyst and the ozone catalyst is (lithium smelting slag + aluminum tailings: bentonite = 6.5:2.5), the maximum compressive strength before activation is 458.6 N / piece (average is 401.8 N / piece), and the average compressive strength after activation is 270 N / piece, which is greater than the national requirement of 150 N / piece.

[0065] like Figure 4 As shown in (e), the ozone catalyst prepared with a mass ratio of (lithium smelting slag + aluminum tailings: bentonite = 6.5: 2.5) has a significant effect on the removal of humic acid in landfill leachate. The fluorescence intensity decreased from >400 a.u. to 150 a.u. and the area of ​​the integral region was greatly reduced.

[0066] Example 5 The preparation process in this example is the same as in Example 1, except that bentonite is added according to the mass ratio (lithium smelting slag + aluminum tailings: bentonite = 6.5: 3).

[0067] like Figure 3 As shown, when the mass ratio of narrow catalyst and ozone catalyst is (lithium smelting slag + aluminum tailings: bentonite = 6.5:3), the maximum compressive strength before activation is 426.4 N / piece (average is 329.7 N / piece). With excessive bentonite and excessive porosity due to high-temperature roasting, the compressive strength after activation is 357 N / piece, which is greater than the national requirement of 150 N / piece.

[0068] like Figure 4 As shown in (f), the ozone catalyst prepared with a mass ratio of (lithium smelting slag + aluminum tailings: bentonite = 6.5: 3) has a significant effect on the removal of humic acid in landfill leachate. The fluorescence intensity decreased from >400 a.u. to 100 a.u. and the area of ​​the integral region was greatly reduced.

[0069] In summary, as the bentonite content increases (6.5:1 to 6.5:2.5), the overall compressive strength of the catalyst gradually increases, but decreases after exceeding 6.5:2.5 (to 6.5:3). The optimal compressive strength is observed in the range of (lithium slag + aluminum tailings):bentonite = 6.5:2 to 6.5:2.5. Furthermore, the higher the bentonite content (6.5:1 to 6.5:2.5), the weaker the characteristic fluorescence of humic acid becomes, with the optimal humic acid degradation performance in the 6.5:2 to 6.5:3 range.

[0070] Comparative Example 1 The preparation process in this example is the same as in Example 1, except that the raw material is a single lithium smelting slag.

[0071] like Figure 8As shown, the prepared catalyst has an uneven surface, poor shape, and an average compressive strength of 3.4 N / particle.

[0072] This disclosure presents a method for preparing an ozone catalyst using lithium smelting slag and aluminum tailings, the ozone catalyst itself, and its application. Compared with the prior art, it has the following advantages: First, this disclosure uses lithium smelting slag and aluminum tailings as the main raw materials to supplement the aluminum shortage in lithium smelting slag. It eliminates the need to purchase aluminum sources such as industrial alumina, thus solving the problem of high production costs due to insufficient aluminum content in lithium smelting slag. At the same time, it digests the stockpiled and difficult-to-use lithium smelting slag, realizing the high-value utilization of solid waste and significantly reducing the cost of catalyst raw materials from the source. Second, this disclosure obtains catalyst particles that are smooth, intact, and crack-free by precisely controlling the silicon-aluminum molar ratio and combining them with bentonite and fiber powder for modification. Under the optimal ratio, the compressive strength can reach 350-450N / particle, which far exceeds the industry standard of 150N / particle. Third, the iron active component of the ozone catalyst prepared by the process disclosed herein is uniformly dispersed inside the molecular sieve channels, with multiple catalytic active sites, high stability, and longer catalyst lifespan. Fourth, the ozone catalyst disclosed herein has excellent removal effect on humic acid and other recalcitrant organic matter in landfill leachate. The fluorescence intensity of the raw water is >400 au, which is reduced to less than 100 au after treatment. The area of ​​the integral region after degradation is greatly reduced, which can efficiently treat recalcitrant COD and meet the upgrading and transformation requirements of biological effluent from sewage treatment plants. At the same time, it can also achieve the adsorption of heavy metals.

[0073] It is understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of this disclosure, and this disclosure is not limited thereto. For those skilled in the art, various modifications and improvements can be made without departing from the spirit and substance of this disclosure, and these modifications and improvements are also considered to be within the scope of protection of this disclosure.

Claims

1. A method for preparing an ozone catalyst using lithium smelting slag and aluminum tailings, characterized in that, The method includes: Lithium smelting slag and aluminum tailings were sequentially ball-milled and sieved. Alkali activator, bentonite, and fiber powder are added to the treated lithium smelting slag and aluminum tailings to obtain composite slag masterbatch. Water was added to the composite slag masterbatch and stirred evenly. After granulation and drying, catalyst carrier microspheres were obtained. The catalyst support microspheres are sintered and then cooled to room temperature to obtain the catalyst support. The catalyst support was immersed in a ferrous nitrate solution and stirred. After being removed, it was dried and activated to obtain an impregnated metal support. The impregnated metal support is calcined to obtain an ozone catalyst.

2. The method according to claim 1, characterized in that, The contents of the lithium smelting slag and the aluminum tailings are calculated as SiO2 and Al2O3, respectively, and their molar ratio n(SiO2 / Al2O3) = (1.1-1.2):1; The contents of the lithium smelting slag and the alkali activator are calculated as SiO2 and Na2O, respectively, and the molar ratio of the two is n(SiO2 / Na2O) = (2.5~3):1; The total content of lithium smelting slag and aluminum tailings to the amount of bentonite added is in a mass ratio of 6.5:(1~3); The mass ratio of the total content of lithium smelting slag and aluminum tailings to the amount of fiber powder added is 6.5:(1~3).

3. The method according to claim 1, characterized in that, The particle size of the catalyst after granulation is 3~6 mm, and the drying temperature is 100-110℃ for 10~14h.

4. The method according to claim 1, characterized in that, The sintering treatment of the catalyst includes: Increase the temperature to 350-450℃ at 5℃ / min, hold for 1.5-2.5 h, then continue to increase the temperature to 750-850℃ at 5℃ / min, hold for 1.5-2.5 h.

5. The method according to claim 1, characterized in that, The catalyst support was immersed in ferrous nitrate solution and stirred at a speed of 200-300 r / min for 2-3 h.

6. The method according to claim 1, characterized in that, After removal, the drying temperature is 100-110℃, and the activation temperature is 90-100℃ for 1-2 hours.

7. The method according to claim 1, characterized in that, The impregnated metal carrier is subjected to a calcination treatment, including: Calcination is carried out at a rate of 5℃ / min to 350-450℃, and the temperature is maintained for 1.5-2.5 hours.

8. An ozone catalyst, characterized in that, The ozone catalyst is prepared by the method described in any one of claims 1-7.

9. The ozone catalyst according to claim 8, characterized in that, The ozone catalyst has a dodecahedral and octahedral single crystal structure with a particle size of 3-5 mm and a bulk density of 0.65-0.75 g / ml.

10. The application of an ozone catalyst, characterized in that, The ozone catalyst described in claim 8 or 9 is used to treat recalcitrant organic pollutants and Pb in landfill leachate. 2+ In the adsorption.